Current and Emerging Biomarkers Predicting Bone Metastasis Development - Iuliani, Michele; Simonetti, Sonia; Ribelli, Giulia; Napolitano, Andrea; Pantano, Francesco; Vincenzi, Bruno; Tonini, Giuseppe; Santini, Daniele (Frontiers in Oncology, 2020)
Bone is one of the preferential site of distant metastases from malignant tumors, with the highest prevalence observed in breast and prostate cancers. Patients with bone metastases (BM) may experience skeletal-related events, such as severe bone pain, pathological fractures, spinal cord compression and hypercalcemia, with negative effects on the quality of life. In the last decades, a deeper understanding of the molecular mechanisms underlying the BM onset has been gained, leading to the development of bone-targeting agents. So far, most of the research has been focused on the pathophysiology and treatment of BM, with only relatively few studies investigating potential predictors of risk for BM development. The ability to select such “high-risk” patients could allow early identification of those most likely to benefit from interventions to prevent or delay BM. This review summarizes several evidences for the potential use of specific biomarkers able to early predict BM development